2018
DOI: 10.1017/s0047279418000715
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Cash Transfers: A Review of the Evidence from Low- and Middle-income Countries

Abstract: This article presents the findings of a review of the impact of non-contributory cash transfers on individuals and households in low- and middle-income countries, covering the literature of 15 years, from 2000 to 2015. Based on evidence extracted from 165 studies, retrieved through a systematic search and screening process, this article discusses the impact of cash transfers on 35 indicators covering six outcome areas: monetary poverty; education; health and nutrition; savings, investment and production; work;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
333
2
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(347 citation statements)
references
References 28 publications
6
333
2
6
Order By: Relevance
“…These figures compare unfavorably to the cost of direct cash transfer programs, recognized as one of the most efficient ways for delivering social assistance to poor households in developing countries—and increasingly advocated as such in developed countries . In Ecuador, half the money spent for the Bono de Desarollo cash transfer program, sometimes described as suffering from targeting problems, goes to one of the 40% poorest household in the country.…”
Section: Getting the Political Economy Right: Domestic Objectives Andmentioning
confidence: 99%
See 1 more Smart Citation
“…These figures compare unfavorably to the cost of direct cash transfer programs, recognized as one of the most efficient ways for delivering social assistance to poor households in developing countries—and increasingly advocated as such in developed countries . In Ecuador, half the money spent for the Bono de Desarollo cash transfer program, sometimes described as suffering from targeting problems, goes to one of the 40% poorest household in the country.…”
Section: Getting the Political Economy Right: Domestic Objectives Andmentioning
confidence: 99%
“…Moreover, instead of the perverse incentives that energy subsidies create, a wealth of ex post empirical studies have found conditional and unconditional cash transfers to reduce poverty, especially on girls and women, improve school attendance (with some evidence of improved cognitive development), increase the uptake of health services, improve dietary diversity and mass and weight indicators, reduce stunting and malnourishment, encourage savings, investment in productive assets and livestock, foster business creation, increase labor force participation for adults and reduce child work, and increase employment rates …”
Section: Getting the Political Economy Right: Domestic Objectives Andmentioning
confidence: 99%
“…7 The vast majority of studies have focused on first-and second-order effects of social assistance programs, mainly in the short and medium term, and on a wide range of issues including household consumption and poverty (Skoufias and Overall, the literature highlights largely positive treatment effects of social assistance on household consumption expenditure and poverty reduction; school enrollment, and attendance-although the evidence on learning outcomes remains ambiguous; health care and anthropometric measures; savings and productive assets such as livestock and agricultural inputs; and in the case of adult labor force participation, and its intensity, studies seems to overwhelmingly reject the proposition that social assistance generates welfare dependency among the poor. The body of evidence; however, varies considerably in terms of the magnitude, direction, and statistical significance of findings across different socioeconomic contexts (Bastagli et al 2019; Barrientos and Niño-Zarazúa 2010; Malerba and Niño-Zarazúa forthcoming).…”
Section: Growing Evidence On the Impact Of Social Assistancementioning
confidence: 99%
“…Consequently, shaming could be a factor involved in the cash transfer effect on schooling if community members observe household behaviors and think that households are not using the money appropriately. In a similar manner, households may initially believe (or be pressured from the community into believing) that there are actually rules attached to cash transfer receipt like enrolling their children in school (Bastagli et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Some evidence has shown that programs can have different schooling effects by gender (Bastagli et al, 2016). In South Africa, for instance, unconditional cash payments from the Old Age Pension had the largest impact on enrollment for girls, and female-headed households were associated with higher enrollment rates (Duflo, 2003).…”
Section: Introductionmentioning
confidence: 99%